Alocação de recursos humanos a tarefas em processos suportados por BPMS - Magalhães, Rui (2018)
In the execution of processes supported by BPMS any task that requires human intervention is delivered to the persons who are designated for the position. The BPMS, will simply send the task for the available resources and those whose name is in the role and will wait for one of them to select the task. This process allows tasks to be performed only by the people who have enough technical capabilities to intervene it, not ensuring that the selected resource is the more qualified person to perform it. The allocation tasks to human resources is of an extreme relevance in the organizations and it is important to taken into account more than just a criteria to select and allocate a resource into a task, the only feature included in this process are the technical skills and it is forgotten the human factor. The human characteristics are also important and need to choose the best human resource to perform the task, for this reason, organizations need to ensure that the resource allocated to the task is the more qualified person. The utilization of business process management systems or BPMS by using an appropriate approach, can contribute to optimize the work conditions in organizations. We intend to demonstrate that in order to optimize the execution of the work performed in the organizations, it is necessary to reconcile the characteristics of the tasks to be executed with the human and social aspects of the people who can perform them.